Digital Banking Transformation Through Cooperation with Fintech Startups in Ukraine - Lobozynska, Sophia; Vladychyn, Ulyana; Skomorovych, Iryna (Journal of Finance and Financial Law, 2023)
The purpose of the article/hypothesis: Is to identify the peculiarities of Fintech startups activities, to track trends and perspectives of interaction between classic banks and Fintech companies, as well as to research the activities of neobanks and formulate proposals for improving the Fintech ecosystem in Ukraine with the aim of providing quality digital financial services to various categories of consumers.Methodology: Methods of statistical analysis, analogy, synthesis and theoretical generalization were used when researching the materials of specialized analytical agencies, official websites of foreign and domestic banks, state financial strategies and scientific literature.Results of the research: The active growth of a number of Fintech startups in the world and in Ukraine forms a positive dynamic of the digital transformation of the banking sector. The cooperation between banks and Fintechs allows the use new innovative products in banking, such as artificial intelligence, robo-consultation, blockchain, cryptocurrencies, the Internet of Things, virtual and augmented reality. For the further digital transformation of banking in Ukraine the financial market participants must implement international open banking standards and tools for remote identification and verification of clients, actively introduce artificial intelligence and machine learning tools into finance, and develop a Fintech ecosystem.